Advancing women's participation in climate action through digital health literacy: gaps and opportunities. (28th September 2022) - Abdolkhani, Robab; Choo, Dawn; Gilbert, Cecily; Borda, Ann
Abstract: Exploring the contribution of health informatics is an emerging topic in relation to addressing climate change, but less examined is a body of literature reporting on the potential and effectiveness of women participating in climate action supported by digital health. This perspective explores how empowering women through digital health literacy (DHL) can support them to be active agents in addressing climate change risk and its impacts on health and well-being. We also consider the current definitional boundary of DHL, and how this may be shaped by other competencies (eg, environmental health literacy), to strengthen this critical agenda for developed nations and lower-resource settings.